Consistent mapping and automatic visual search: comparing persons with and without intellectual disability. - Merrill EC (Journal of Intellectual Disability Research, 2004)
BACKGROUND: Merrill et al. (1996) reported that persons with intellectual disability (ID) were slower at learning a visual search task to automaticity relative to persons of the same age without ID. For persons without ID, automaticity develops most rapidly under conditions in which a response is always the same for a particular stimulus. This study was designed to investigate whether persons with and without ID are differentially sensitive to the influence of consistently mapped versus inconsistently mapped stimulus responses. METHODS: The primary manipulation was the consistency between a particular stimulus and the response to that stimulus in a visual search task. Sixteen participants with ID and 16 without ID searched displays of two, three, or four pictured objects to determine if a target was present. For half of the participants, the targets were always targets. For the other half, the targets became nontargets on 25% of the trials. RESULTS: Analyses focused on changes in response times associated with set size. Because automaticity allows for parallel processing, the elimination of significant effects of set size was taken as an index of the development of automaticity. Results indicated that inconsistent mapping significantly slowed the development of automaticity for the participants without ID but not for the participants with ID. DISCUSSION: Results were discussed in terms of the role of inhibition processes in the development of automatic search and detection. The effectiveness of inhibition processes was compromised by the consistency manipulation. The effect of the consistency manipulation was greater for the participants without ID because they were presumed to be using inhibition processes more effectively during practice than did the participants with ID.